2017
DOI: 10.1038/s41598-017-10819-8
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive aggregation by spider mites under predation risk

Abstract: Grouping together is a commonly observed anti-predator strategy. Possible anti-predator benefits of aggregation include the encounter/avoidance effect for visually hunting predators and the dilution effect, together dubbed attack abatement. Possible costs opposing the dilution effect are easier detection of aggregated than scattered individuals. The benefits of attack abatement, and opposing costs after group detection, are poorly understood for chemosensory predator-prey interactions. We tackled this issue by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…Pioneers are later paid back by being released from costly individual web production and other aggregationrelated benefits such as enhanced mating opportunities and enhanced protection from predators (see also the section on web sharing under predation risk), and other abiotic and biotic hazards for themselves and their offspring. Joining other groups and tightening the levels of aggregation enhance the chances of survival under predation risk because of attack abatement, even when the webbing is light or absent (Dittmann and Schausberger, 2017). An intriguing example of non-kin interactions comes from Schausberger et al (2019), who showed that individuals of one population heavily benefited (without any direct interactions) from microhabitat manipulation by webbing or host plant biochemistry by pioneering colonizers from another population (Y coming to G environment), whereas in the reverse sequence, later arrivers were negatively affected (G coming to Y environment).…”
Section: Host Plant Colonization and Exploitation By Tetranychus Sppmentioning
confidence: 99%
“…Pioneers are later paid back by being released from costly individual web production and other aggregationrelated benefits such as enhanced mating opportunities and enhanced protection from predators (see also the section on web sharing under predation risk), and other abiotic and biotic hazards for themselves and their offspring. Joining other groups and tightening the levels of aggregation enhance the chances of survival under predation risk because of attack abatement, even when the webbing is light or absent (Dittmann and Schausberger, 2017). An intriguing example of non-kin interactions comes from Schausberger et al (2019), who showed that individuals of one population heavily benefited (without any direct interactions) from microhabitat manipulation by webbing or host plant biochemistry by pioneering colonizers from another population (Y coming to G environment), whereas in the reverse sequence, later arrivers were negatively affected (G coming to Y environment).…”
Section: Host Plant Colonization and Exploitation By Tetranychus Sppmentioning
confidence: 99%
“…Large groups of prey may be more conspicuous to predators (Ioannou et al 2009), but this effect often saturates at high prey densities (Riipi et al 2001). This may lead to a benefit of prey aggregation, where the cost to prey of increased apparency is outweighed by the benefit of having fewer groups occupying the same search area (Ioannou et al 2011, Dittman and Schausberger 2017). Once a predator enters a prey patch, the risk for individual prey then depends on within‐patch search behavior and consumption.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting extension of the model presented here would be to include interactions which affect the proliferation and mortality of individuals, such as predator-prey interactions or intra and interspecific competition 44,45 . The population dynamics resulting from such interactions will depend on the types of spatial structure examined in this work.…”
Section: Discussionmentioning
confidence: 99%